(untitled) (Acta Polytechnica CTU Proceedings, 2023)
The 13th conference Nano & Macro Mechanics was held in Prague, in September 15, 2022. The main objective of the conference is to bring together researchers, students and engineers devoting their work to comuting and experimental mechanics in different areas of engineering applications on a common platform. The conference key topics were following: • Testing of building materials at the nano and macro level. • Destructive and non-destructive methods for determining the mechanical properties of building materials. • Relationships between material parameters at nano and macro level. • Numerical simulation of behavior of structures and materials. • Computational and experimental dynamics and mechanics. • Material research for steel, building materials, glass, woods, textiles, and composites. • Analyses of constructions. • Computational methods for analyses of the constructions. • Biomechanics. Scientific comittee: Tomáš Plachý Pavel Tesárek Pavel Padevět Petr Bittner Aleš Jíra Jan Vorel Lenka Mezerová Michal Šejnoha Bořek Patzák Local organizing comittee: Petr Bittner Tomáš Plachý Pavel Padevět Pavel Tesárek Ondřej Zobal Barbora Mužíková Zdeněk Prošek Guarantor of the peer review process: Pavel Padevět Guarantor of the language editing: Tomáš Plachý